Identification and Characterization of DAMs Mutations Associated With Early Blooming in Sweet Cherry, and Validation of DNA-Based Markers for Selection - Calle, Alejandro; Grimplet, Jérôme; Le Dantec, Loïck; Wünsch, Ana (Frontiers in Plant Science, 2021)
Dormancy release and bloom time of sweet cherry cultivars depend on the environment and the genotype. The knowledge of these traits is essential for cultivar adaptation to different growing areas, and to ensure fruit set in the current climate change scenario. In this work, the major sweet cherry bloom time QTL qP-BT1.1m (327 Kbs; Chromosome 1) was scanned for candidate genes in ‘Regina’ cv genome. Six MADS-box genes (PavDAMs), orthologs to peach and Japanese apricot DAMs, were identified as candidate genes for bloom time regulation. The complete curated genomic structure annotation of these genes is reported. To characterize PavDAMs intra-specific variation, genome sequences of cultivars with contrasting chilling requirements and bloom times (N=13), were then mapped to the ‘Regina’ genome. A high protein sequence conservation (98.8-100%) was observed. A higher amino acid variability and several structural mutations were identified in the low-chilling and extra-early blooming cv ‘Cristobalina’. Specifically, a large deletion (694 bp) upstream of PavDAM1, and various INDELs and SNPs in contiguous PavDAM4 and -5 UTRs were identified. PavDAM1 upstream deletion in ‘Cristobalina’ revealed the absence of several cis-acting motifs, potentially involved in PavDAMs expression. Also, due to this deletion, a non-coding gene expressed in late-blooming ‘Regina’ seems truncated in ‘Cristobalina’. Additionally, PavDAM4 and -5 UTRs mutations revealed different splicing variants between ‘Regina’ and ‘Cristobalina’ PavDAM5. The results indicate that the regulation of PavDAMs expression and post-transcriptional regulation in ‘Cristobalina’ may be altered due to structural mutations in regulatory regions. Previous transcriptomic studies show differential expression of PavDAM genes during dormancy in this cultivar. The results indicate that ‘Cristobalina’ show significant amino acid differences, and structural mutations in PavDAMs, that correlate with low-chilling and early blooming, but the direct implication of these mutations remains to be determined. To complete the work, PCR markers designed for the detection of ‘Cristobalina’ structural mutations in PavDAMs, were validated in an F2 population and a set of cultivars. These PCR markers are useful for marker-assisted selection of early blooming seedlings, and probably low-chilling, from ‘Cristobalina’, which is a unique breeding source for these traits.